Exosomes promote restoration after an experimental animal model of intracerebral hemorrhage - Otero-Ortega, Laura (J Cereb Blood Flow Metab, 2017)
Exosomes are gaining importance because they show great promise in therapeutic applications for several diseases. Particularly in stroke, exosomes derived from mesenchymal stem cell (MSC) therapy work as paracrine effectors responsible for promoting neurovascular remodeling and functional recovery. Adult male rats were subjected to intracerebral hemorrhage (ICH) by intrastriatal injection of collagenase type IV; 24 h after surgery, MSC-derived exosomes were administered through the tail vein. The rats were euthanized at 7 or 28 days after treatment. Functional evaluation, lesion size, fiber tract integrity, axonal sprouting and white matter repair markers, biodistribution of exosomes and secretome proteomics were analyzed. DiI-labeled exosomes were found in the brains of the ICH-treated group and in the liver, lung and spleen. Animals receiving treatment with exosomes showed significantly better results in terms of functional recovery, lesion size, fiber tract integrity, axonal sprouting and white matter repair markers compared with the control group 28 days after stroke. Proteomics analysis of the exosomes identified more than 2000 proteins that could be implicated in brain repair function. In conclusion, white matter integrity was partly restored by exosome administration mediated by molecular repair factors. Exosomes as a treatment could be a heterogeneous process by nature and presents many factors that can influence brain plasticity in an adaptable and versatile manner.